Relationship Between Mother’s Knowledge of Rubella with Measles Rubella (MR) Immunization Status in Children Age 9-59 Months at MR Campaign, Java Island - Indonesia 2017 (Indian Journal of Public Health Research & Development, 2020)
Background: MR (Measles Rubella) campaign is one of Indonesia’s efforts to achieve the world targetwithout measles, rubella, and Congenital Rubella Syndrome (CRS) in 2020. However, the results show thatMR campaign immunization coverage is not optimal. This study aims to determine whether the knowledgeof mothers about rubella is related to MR immunization status in MR campaign at Java Island.Method: This cross-sectional study used secondary data from the survey of Independent Evaluation of MRImmunization in 6 provinces at Java Island in 2017. There were 5,971 samples of mothers who had childrenaged 9-59 months were obtained based on cluster sampling technique. Bivariate and multivariate analysiswere used to see the relationship between mother’s knowledge of rubella and MR immunization status.Result: Mother’s knowledge about rubella interacted with belief (POR 1,899 95% CI 1,267-2,848) andinteracted with education (POR 1,675 95% CI 1,086-2,583) to form a statistically significant relationshipwith MR immunization status.Conclusion: Mother’s knowledge of rubella is very important in increasing MR immunization coverage.Therefore, the government is expected to cooperate with active stakeholders to provide information on MRimmunization.
Keywords: Mother’s knowledge, MR campaign